Faktor-faktor yang Berhubungan dengan Ancaman Partus Prematurus di Rumah Sakit Bhakti Mulia Jakarta Barat Tahun 2024 - Jamilah Jamilah; Widowati Pusparini (Universitas Pahlawan Tuanku Tambusai, 2025)
Bhakti Mulia Hospital, West Jakarta, in 2023 found 10 cases of infant death. Premature birth remains the main cause of neonatal death. Some of the factors that influence premature birth are maternal factors, namely age less than twenty years or more than 35 years, pregnancy and delivery too close together, and a history of premature birth.to determine the factors associated with the threat of premature parturition at Bhakti Mulia Hospital, West Jakarta in 2024.Quantitative analytical research with a cross sectional design. The research sample of pregnant women from January to October 2024 was 285 respondents using a simple random sampling technique. Secondary data using a checklist sheet was analyzed using the square test.The results of univariate analysis showed that the majority of pregnant women did not experience the threat of preterm labor, 86.0%, age was not at risk, 84.6%, pregnancy interval > 24 months, 77.2% and no history of preterm labor, 81.8%. The results of bivariate analysis showed a relationship between age (p value = 0.000), pregnancy spacing (p value = 0.000) and history of preterm labor (p value = 0.000) with the threat of preterm labor.age, gestational spacing and history of preterm labor are associated with the threat of preterm labor. Pregnant women are expected to be able to prepare themselves for their pregnancies to prevent premature birth, including paying attention to food intake with a balanced nutritional menu, maintaining a pregnancy gap of more than 2 years for the previous child, and carrying out regular pregnancy checks so that early detection can be carried out if the mother experiences pregnancy complications.